INTERNATIONAL COMPETITIVENESS OF ASEAN REGIONAL INTEGRATION (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: In addition to being one of the major regional integrations, owing to its favorable geopolitical position, demographic indicators, and economic power, the Association of Southeast Asian Nations (ASEAN) is also one of the world’s largest and most influential economic superpowers. This paper aims to examine the international competitiveness and trade of ASEAN member states.Methodology: The research methodology is based on the use of a group of indicators of trade balance, intra-industry trade, the share of exports in imports, trade openness, and the share of exports in GDP in the period from 2013 to 2017.Results: The main results of the paper refer to the evaluation of the competitive position of ASEAN member states’ in international terms (Indonesia, Malaysia, Philippines, Singapore, Thailand, Brunei Darussalam, Vietnam, Laos, Myanmar, and Cambodia), as well as to the aggregated results of ASEAN regional integration indicators.Conclusion: The paper’s concluding remarks are an attempt to determine the trading position of ASEAN member states and provide recommendations on how to enhance their international competitiveness.